Role Playing Game Tanpa Gadget (Penelitian Tindakan Kelas dalam Pembelajaran Sejarah di Kelas XI IPS C MAN I Kota Bandung) - Tio Faturhoman; Tarunasena Tarunasena (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2019)
Ideally, the students’ goal in carrying out the activities of learning is to obtain behavioural change. But it was contradictory wherein the reality found during observations in Grade XI IPS C. During learning History takes place, students were doing activities that improper with the learning agenda. The cause as the use of learning methods thatirrelevant to each student’s character. Based on the results’ observations, the author realized the proper method for students of Grade XI IPS C is Role Playing. Therefore the author conducted a classroom action research with the research formulation “Howto apply the Role Playing method in learning History to improve directed learning activities for students of Grade XI IPS C in MAN I Bandung?” This Classroom Action Research (CAR) based on Kemmis Taggart design. In this design, CAR is carried out in several cycles which are divided into 4 (four) stages namely: Planning, Action,Observation and Reflection. After applying the Role Playing method, the author found an increasing towards student learning activities both physically and mentally. Thus it can be concluded that the Role Playing method is strongly effective in directing student activities in learning History.